Meta-analysis: on average, undergraduate students’ intelligence is merely average - Bob Uttl; Victoria Violo; Lacey Gibson (ScienceOpen Research)
According to a widespread belief, the average IQ of university students is 115 to 130 IQ points, that is, substantially higher than the average IQ of the general population ( M = 100, SD = 15). We traced the origin of this belief to obsolete intelligence data collected in 1940s and 1950s when university education was the privilege of a few. Examination of more recent IQ data indicate that IQ of university students and university graduates dropped to the average of the general population. The decline in students’ IQ is a necessary consequence of increasing educational attainment over the last 80 years. Today, graduating from university is more common than completing high school in the 1940s. We conducted a meta-analysis of the mean IQ scores of college and university students samples tested with Wechsler Adult Intelligence Scale between 1939 and 2022. The results show that the average IQ of undergraduate students today is a mere 102 IQ points and declined by approximately 0.2 IQ points per year. The students’ IQ also varies substantially across universities and is correlated with the selectivity of universities (measured by average SAT scores of admitted students). These findings have wide-ranging implications. First, universities and professors need to realize that students are no longer extraordinary but merely average, and have to adjust curricula and academic standards. Second, employers can no longer rely on applicants with university degrees to be more capable or smarter than those without degrees. Third, students need to realize that acceptance into university is no longer an invitation to join an elite group. Fourth, the myth of brilliant undergraduate students in scientific and popular literature needs to be dispelled. Fifth, estimating premorbid IQ based on educational attainment is vastly inaccurate, obsolete, not evidence based, and mere wishful thinking. Sixth, obsolete IQ data or tests ought not to be used to make high-stakes decisions about individuals, for example, by clinical psychologists to opine about the intelligence and cognitive abilities of their clients.